Sapphire Material, Manufacturing, Applications - Pishchik, Valerian. (Micro- and Opto-Electronic Materials, Structures, and Systems, 2009)
Sapphire: Material, Manufacturing, Applications provides complete coverage of sapphire crystal growth and fabrication, including important information on the physical, mechanical, and chemical properties. This book considers all known methods for the growth of sapphire and modification of its properties and includes the most exhaustive data on the crystal structure and physical-chemical properties. Written by leading experts in the field of sapphire crystals, this book presents many various applications, including use in quantum electronics, radio electronics, radio engineering, radiolocation, ultrahigh resolution optics, high temperature optics, aircraft applications, atomic power engineering, and microwave engineering. Sapphire: Material, Manufacturing, Applications addresses the unusual, versatile and attractive physical and chemical properties of sapphire, as well as the trends in growth methods, and will be useful to specialists in crystal growth technologies, engineers and scientists who utilize sapphire in their work.